Establishing arbitrary comparative relations and referential transformations of stimulus function in individuals with autism. Issue 2 (25th October 2019) - Belisle, Jordan; Stanley, Caleb R.; Schmick, Ayla; Dixon, Mark R.; Alholail, Amani; Galliford, Megan E.; Ellenberger, Lindsey
Abstract : Relational Frame Theory posits that complex language develops through arbitrarily applicable relational networks, with potential implications for individuals with autism. Responding relationally based on comparison occurs when participants respond to any number of comparative properties, such as "bigger" or "faster." Experiment 1 established two 3‐member comparative networks, in which a stimulus A was conditioned as "bigger" or "faster" than a stimulus B, and the stimulus B was conditioned as "bigger" or "faster" than a stimulus C in 2 children with autism. Both participants met the mastery criterion for the trained relations and demonstrated the emergence of the untrained combinatorially entailed A–C and C–A relations. The participants could also match the arbitrary A stimuli with larger or faster objects and the C stimuli with smaller or slower objects. The results were replicated in Experiment 2 with the same participants, where a 5‐member relational network was established for the bigger/smaller relation.